2021
DOI: 10.1002/ejp.1811
|View full text |Cite
|
Sign up to set email alerts
|

Placebo effects in low back pain: A systematic review and meta‐analysis of the literature

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 56 publications
1
7
0
1
Order By: Relevance
“…Anyhow, we consider (based on the confidence intervals) most effects on pain as probably clinically relevant when individualised exercises are compared to passive measures or other exercises. The clinical relevance may be strengthened due to the following reasons: i) adding a stratification and /or personalisation to the exercise intervention is simple and almost time and cost neutral, ii) at 12 weeks pain intensity was reduced by individualised exercise by 40% and at 26 weeks by 38%, which from a patient's perspective is of clear benefit, iii) all results are at least consistent in the point that there is a trend (or, even, mostly a significant betweengroup difference leading to a probable relevant effect) towards individualised treatments that becomes larger when not comparing to active but passive controls, iv) taking into account the strong known placebo effects in low back pain 43 emphasizes the small effects retrieved in our study. As all studies were patient-examiner blinded -what hands-on trials cannot be blamed for-this observation seems robust.…”
Section: Discussionmentioning
confidence: 62%
“…Anyhow, we consider (based on the confidence intervals) most effects on pain as probably clinically relevant when individualised exercises are compared to passive measures or other exercises. The clinical relevance may be strengthened due to the following reasons: i) adding a stratification and /or personalisation to the exercise intervention is simple and almost time and cost neutral, ii) at 12 weeks pain intensity was reduced by individualised exercise by 40% and at 26 weeks by 38%, which from a patient's perspective is of clear benefit, iii) all results are at least consistent in the point that there is a trend (or, even, mostly a significant betweengroup difference leading to a probable relevant effect) towards individualised treatments that becomes larger when not comparing to active but passive controls, iv) taking into account the strong known placebo effects in low back pain 43 emphasizes the small effects retrieved in our study. As all studies were patient-examiner blinded -what hands-on trials cannot be blamed for-this observation seems robust.…”
Section: Discussionmentioning
confidence: 62%
“…Hence, the effects of SMT against placebo or sham SM remain uncertain. This parallels the state of research on most interventions for spine pain, as no treatment has been demonstrated to be superior to any other or to placebo (126)(127)(128). It could be argued that effective treatments for LBP and NP have a large share of non-specific effects.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 88%
“…Through altering expectations, shifting mood, and providing social support, placebo treatments have been shown to decrease perceptions of pain [ 43 ]. A recent meta-analysis of patients with LBP also showed significant placebo effects for pain intensity and LBP-related disability [ 44 ]. Future studies should further investigate the expectation of improvement based on interventions.…”
Section: Discussionmentioning
confidence: 99%